IMPLEMENTATION OF ENTREPRENEURSHIP EDUCATION DEVELOPING CREATIVE THINKING OF GRADE XI VOCATIONAL STUDENTS THROUGH CREATIVE PROJECTS - Alfiatul Ma’rifah; Hety Mustika Ani; Tiara Tiara; Sela Rachmawati (Universitas Muhammadiyah Metro, 2026)
ABSTRACT Entrepreneurship education in vocational high schools plays a crucial role in preparing students for work or entrepreneurship by developing their creative thinking skills. Low creative thinking skills cause students to be less innovative, passive, and uncompetitive. This study aims to describe the implementation of entrepreneurship education in the Creative Project and Entrepreneurship subject in shaping students' creative thinking skills. This study uses a qualitative descriptive approach implemented at SMK Negeri 1 Jember. The research participants consisted of Creative Project and Entrepreneurship subject teachers, as well as four students from class XI at the Industry. Data collection techniques include interviews, observations, and documents. Data analysis included data reduction, data presentation, and conclusion. Data validity was obtained through source triangulation. The results of the study indicate that the implementation of entrepreneurship education in the Creative Project and Entrepreneurship subject, utilizing business opportunities material, was carried out according to process standards, including planning, implementation, and assessment. Creative thinking skills were measured through aspects of fluency, flexibility, originality, and elaboration. Keywords: creative project and entrepreneurship; creative thinking skills; entrepreneurship education; vocational student ABSTRAK Pendidikan kewirausahaan SMK memiliki peran strategis dalam menyiapkan peserta didik agar siap bekerja maupun berwirausaha melalui pengembangan kemampuan berpikir kreatif. Namun, rendahnya kemampuan berpikir kreatif siswa menyebabkan kurangnya inovasi, sik ap pasif, serta rendahnya daya saing. Penelitian ini bertujuan untuk mendeskripsikan implementasi pendidikan kewirausahaan pada mata pelajaran Projek Kreatif dan Kewirausahaan dalam membentuk kemampuan berpikir kreatif siswa. Penelitian menggunakan pendeka tan deskriptif kualitatif yang dilaksanakan di SMK Negeri 1 Jember. Partisipan penelitian terdiri atas satu guru mata pelajaran Projek Kreatif dan Kewirausahaan serta empat siswa kelas XI Industri. Teknik pengumpulan data dilakukan melalui wawancara, obser vasi, dan dokumentasi. Analisis data dilakukan melalui tahapan reduksi data, penyajian data, dan penarikan kesimpulan, sedangkan keabsahan data diperoleh melalui triangulasi sumber. Hasil penelitian menunjukkan bahwa implementasi pendidikan kewirausahaan pada materi peluang usaha telah dilaksanakan sesuai standar proses pembelajaran yang meliputi tahap perencanaan, pelaksanaan, dan penilaian. Kemampuan berpikir kreatif siswa berkembang melalui empat aspek, yaitu kelancaran, keluwesan, orisinalitas, dan elaborasi. Simpulan penelitian ini menunjukkan bahwa pembelajaran Projek Kreatif dan Kewirausahaan berperan positif dalam membentuk kemampuan berpikir kreatif siswa SMK. Kontribusi penelitian ini memberikan penguatan secara konseptual dan praktis terhadap pengembangan pendidikan kewirausahaan sebagai sarana peningkatan kemampuan berpikir kreatif dalam konteks pendidikan vokasi. Kata Kunci : kemampuan berpikir kreatif; pendidikan kewirausahaan; projek kreatif dan kewirausah